Relationship Between Clinical Competency and Moral Courage in Iranian Nurses Working in Teaching Hospitals - Mohammad Farzanehfar; Sowgand Bahadori Hamraz; Arezou Karampourian; Salman Khazaei (Iran University of Medical Sciences, 2023)
Background & Aims Providing quality nursing care has always been the main concern of nurses. Clinical competence and moral courage are effective factors in providing quality nursing care. The present study aims to determine the relationship between clinical competency and moral courage in Iranian nurses. Materials & Methods This is a descriptive-correlational study with a cross-sectional design that was conducted in 2022 on 123 nurses working in teaching hospitals affiliated to Hamadan University of Medical Sciences, who were selected using a simple random sampling method. Data collection tools were Sekarka et al.'s moral courage questionnaire, Liu et al.'s competency inventory for registered nurses, and a demographic form. Data analysis was done using descriptive statistics, independent t-test, one-way analysis of variance and Pearson's correlation test in SPSS software, version 16. Results The mean scores of clinical competency and moral courage scores were 151.18‌±‌22.32 and 59.56‌±‌7.47, respectively, indicating a moderate clinical competency and high moral courage. There was a significant and positive (weak) relationship between moral courage and clinical competency (r=0.272, P=0.001). Conclusion Due to the moderate clinical competency of nurses, educational workshops are recommended to improve their clinical competence. Moreover, since there is a weak relationship between clinical competency and moral courage of nurses, factors other than clinical competence may be related to moral courage, which requires further studies.